Senam Sehat dalam Meningkatkan Imun Tubuh pada Masa Pandemi Covid 19 di Desa Peringgasela Selatan - Muhammad Husni Tamim; Rina Nopiana (Indonesian Institute For Counseling, Education and Therapy, 2020)
Doing physical activity can make the body fit and increase the body's immunity to be able to fight the virus during the Covid-19 pandemic. Based on this, sports activities are needed to invite people to maintain their physical health through healthy exercise activities which are held aimed at increasing people's interest in exercising during the Covid-19 pandemic during new normal so that their body endurance is better. This community service (PKM) is a form of real work from the Hamzanwadi University Physical Education and Health Study Program for the people of South Pringgasela Village to participate in healthy gymnastics as an effort to prevent Covid-19. Healthy gymnastics activities can increase public awareness of the importance of maintaining health in the era of the Covid-19 pandemic.